The Implementation of Teaching English Using Differentiated Instruction in Senior High School during Covid-19 Pandemic - Pande Nyoman, Satyarini; Ni Nyoman , Padmadewi; Made Hery , Santosa (Universitas Pendidikan Ganesha, 2022)
A large number of teachers are adopting one-size-fits-all teaching instruction for all students. However, the diversity of student characteristics should require teaching strategies that can meet various mixed abilities in the classroom. The study focused on analyzing the implementation of differentiated instruction and investigating the challenges encountered by the teacher in implementing differentiated instruction in teaching during the pandemic of Covid-19 in Senior High School. This research uses a descriptive qualitative research design assisted by observation and an interview. The researcher, observation sheet, interview guide, and documents were used as instruments to obtain the data. The participants of the study consisted of the researcher, an English teacher, and thirty-six students from class PBB 1. The data of the study were analyzed through components of the data analysis interactive model which included three concurrent activities such as data condensation, data display, and conclusion drawing and verification. The findings showed the implementation of differentiated instruction was partial. The teacher differentiated content, process, and product by following students' interests and learning profiles. However, the differentiation based on student readiness levels was not visible. The teacher only used eLearning, Zoom Video Conference, and WhatsApp groups, similar to how teachers commonly conducted online learning. In using differentiated instruction, the teacher encountered challenges associated with students' participation in a virtual class, a large number of students, a lack of time for planning, and group activities in learning that were limited.